Stroop interference associated with efficient reading fluency and prelexical orthographic processing. Issue 3 (15th March 2016) - Mano, Quintino R.; Williamson, Brady J.; Pae, Hye K.; Osmon, David C.
ABSTRACT: The Stroop Color–Word Test involves a dynamic interplay between reading and executive functioning that elicits intuitions of word reading automaticity. One such intuition is that strong reading skills (i.e., more automatized word reading) play a disruptive role within the test, contributing to Stroop interference. However, evidence has accumulated that challenges this intuition. The present study examined associations among Stroop interference, reading skills (i.e., isolated word identification, grapheme-to-phoneme mapping, phonemic awareness, reading fluency) measured on standardized tests, and orthographic skills measured on experimental computerized tasks. Among university students ( N = 152), correlational analyses showed greater Stroop interference to be associated with (a) relatively low scores on all standardized reading tests, and (b) longer response latencies on orthographic tasks. Hierarchical regression demonstrated that reading fluency and prelexical orthographic processing predicted unique and significant variance in Stroop interference beyond baseline rapid naming. Results suggest that strong reading skills, including orthographic processing, play a supportive role in resolving Stroop interference.